Pemilihan Kost di Sekitar Universitas Brawijaya Menggunakan Metode Analitycal Hierarchy Process (AHP) dan Simple Additive Weighting (SAW) - Putra Aditya Primanda; Edy Santoso; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
For students who study in Universitas Brawijaya they can live in Malang city by various ways that is by buying a house in Malang, living in dormitory, house contract or boarding area around Universitas Brawijaya. Kost is a solution for students who study in Malang as a place to live. But with the number of kost around UB Brawijaya sometimes students will often move the boarding place for several reasons namely the increasingly expensive rental, the convenience of boarding place, the location of boarding away from the University, where the boarding away from where to eat or layout Which is away from the main road. So to cope with this, it is necessary to select the most suitable boarding place. In choosing this boarding place can use the method of Analytic Hierarchy Process (AHP) and Simple Additive Weighting (SAW) to get a good boarding place. From the tests that have been done that the number of criteria is very influential in the ranking results. The highest percentage of matches against 7 criteria were 6 criteria with 8.831% then 5 criteria with 7.999%, 4 criteria with 4.761%, 3 criteria with 3.58%, 2 criteria and 1 criterion with 0%. The tests show that many of the criteria used influence the recommended boarding outcomes based on the number of criteria used.